Company Financial Strategy’s Instituonalization: Theoretical Aspects - ALEKSIN, G. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
Under today’s conditions of exogenous and endogenous challenges for economic agents, the problem of ensuring value creation for stakeholders on a long-term horizon is becoming more acute. The lack of adequately formed institutions within Ukraine’s market infrastructure adds additional complexity to the task. The aim of this paper is to identify the features of an effective financial strategy institute in Ukraine. This paper examines issue of forming and further functioning of financial strategy institute at company, industry, and state level. The problems of Ukrainian corporate sector genesis in the context of the formation of market institutions are described. The effect of information asymmetry and principal-agent conflict on the process and results of value creation for stakeholders is highlighted. Ways to reduce the influence of the principal-agent conflict through institutionalization are proposed. Paper also considers financial strategy’s institutionalization as a factor influencing investors’ interest in the company is considered. It is noted that the existing incentive tools for the company’s managers are aimed at the short-term horizon. It is emphasized that the financial strategy’s institutionalization would contribute to overcoming excessive fixation on the company’s short-term results, instead, an adequate balance would be formed regarding short- and long-term priorities at the company level. Financial strategy institute’s placement in the company’s management architecture is defined. The conducted research may be useful for researchers in the field of corporate governance and corporate finance, private and state- owned companies, industry associations, and state authorities. Prospects for future research are an in-depth analysis of the financial strategy institute’s infrastructure, in particular, in terms of its quantitative analysis and evaluation.